(untitled) (Biological Sciences - PJSIR, 2009)
Assessment of the amount of plant available sulphur (SO4-S) in soils of Pothwar, Pakistan revealed the average S contents in the soil to range from 5.7 to 21.7 ?g/g. Five out of fifteen soil series were deficient (< 10 ?g S/g) in SO4-S with a range of 5.0 to 9.0 ?g/g, six were deficient only at upper (0-15 cm) soil depth while, the remaining four had satisfactory level (10-30 ?g S/g) at both the soil depths. Sulphur exhibited significant positive correlation with clay (r = 0.77**), EC (r = 0.77**), organic C (r = 0.82**), total N (r = 0.88**) and extractable P (r = 0.72**) contents in soil. Correlation coefficients of SO -S with sand (r = -0.41), soil pH (r = -0.49) and CaCO (r = -0.60*) contents were negative. Organic C and N had the most pronounced effects (R2 > 65) on S availability in soil.